Infrastructure Divergence And Its Impact On Economic Growth In West Nusa Tenggara - Nur Fadilah; Wahyunadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Infrastructure growth in West Nusa Tenggara (NTB) has shown uneven development at both the regional and sectoral levels in the last 10 years. This study examines how road, electricity and water infrastructure across the regions of NTB affect the economic growth considering interregional development divergence. An empirical approach was taken through panel data regression estimation with Random Effects specification, covering 100 observation units. Results indicate that there is a positive but insignificant relationship between that water infrastructure and economic growth, while road and electricity infrastructure have a positive and significant relationship. Although the models ability to explain variations in economic growth is relatively limited, the simultaneous effect of the three types of infrastructure remains significant. Overall, these findings that infrastructure contribution to the economic growth does not have a homogenous effect on the growth of regions. The results suggest the need for integrated infrastructure development policies that focus on improving service quality and road network connectivity need to be considered.